2022
DOI: 10.48550/arxiv.2201.07802
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clifford-deformed Surface Codes

Abstract: Various realizations of Kitaev's surface code perform surprisingly well for biased Pauli noise. Attracted by these potential gains, we study the performance of Clifford-deformed surface codes (CDSCs) obtained from the surface code by the application of single-qubit Clifford operators. We first analyze CDSCs on the 3 × 3 square lattice and find that depending on the noise bias, their logical error rates can differ by orders of magnitude. To explain the observed behavior, we introduce the effective distance d , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…While the XZZX and subsystem surface codes both offer improved performance compared to the CSS surface code near threshold for biased circuit-level noise [9,10], a more detailed analysis will be required to assess whether this also translates into a reduced qubit overhead for a noise regime of practical interest below threshold. The CSS, XY and XZZX surface codes all fall within the broader family Clifford-deformed surface codes [45], which provide even more flexibility for tailoring the surface code to the noise bias, and further work is required to investigate these codes in a fault-tolerant setting. Finally, for architectures with improved qubit connectivity, it is possible that bias-tailored quantum LDPC codes will offer a further reduction in qubit overhead [25].…”
Section: Discussionmentioning
confidence: 99%
“…While the XZZX and subsystem surface codes both offer improved performance compared to the CSS surface code near threshold for biased circuit-level noise [9,10], a more detailed analysis will be required to assess whether this also translates into a reduced qubit overhead for a noise regime of practical interest below threshold. The CSS, XY and XZZX surface codes all fall within the broader family Clifford-deformed surface codes [45], which provide even more flexibility for tailoring the surface code to the noise bias, and further work is required to investigate these codes in a fault-tolerant setting. Finally, for architectures with improved qubit connectivity, it is possible that bias-tailored quantum LDPC codes will offer a further reduction in qubit overhead [25].…”
Section: Discussionmentioning
confidence: 99%
“…In Ref. [22], it is shown that random Clifford deformations of the CSS surface codes can lead to better codes. It is worth investigating whether a similar transformation can boost the performance of our XZZX codes.…”
Section: Discussionmentioning
confidence: 99%
“…To estimate the performance of different error-correcting codes under the asymmetric channel, we define the effective distance d of a stabilizer code as the minimum modified weight of logical operators, with the noise-modified weight of a Pauli σ given by wt (σ) ≡ log p σ /N , where N is a normalization factor; see Ref. [22] for an alternative but related definition of the effective code distance. To normalize the effective weight of the most probable Pauli error to 1, we choose N = log p m .…”
Section: Effective Code Distance For Asymmetric Pauli Noisementioning
confidence: 99%
See 1 more Smart Citation
“…By modifying the stabilizers of the surface code [31] by local Pauli frame change, one can generate the tailored [25][26][27] or XZZX [28] surface codes (see Fig. 1) as well as other Clifford-deformed surface codes [32], all of which have much higher thresholds than the standard surface code in the presence of biased noise [25? -28].…”
Section: Introductionmentioning
confidence: 99%